Animism and natural teleology from Avicenna to Boyle. Issue 1 (March 2021) - Kochan, Jeff
Argument: Historians have claimed that the two closely related concepts of animism and natural teleology were both decisively rejected in the Scientific Revolution. They tout Robert Boyle as an early modern warden against pre-modern animism. Discussing Avicenna, Aquinas, and Buridan, as well as Renaissance psychology, I instead suggest that teleology went through a slow and uneven process of rationalization. As Neoplatonic theology gained influence over Aristotelian natural philosophy, the meaning of animism likewise grew obscure. Boyle, as some historians have shown, exemplifies this uneven process. There is an unresolved tension between his religious convictions and the implicit animism of his empirical practice.